Principles and Procedures of the Construction of Opera Scenarios - BOURCEANU, Mădălina Gabriela (Studia Universitatis Babes-Bolyai Musica, 2023)
The construction of opera scenarios involves the development of a dramatic and narrative framework upon which an opera is built. These scenarios serve as the foundation for the libretto, music, staging, and overall production of the opera. In this introduction, we will explore the principles and procedures that guide the creation of opera scenarios. In summary, constructing an opera scenario is a complex and collaborative process that involves the careful consideration of narrative, character, music, and cultural context. The principles and procedures outlined here provide a foundation for the creation of opera scenarios that can captivate audiences and convey the depth of human emotion through music and drama. Over time, the evolution of the singing voice follows a phenomenon of symbiosis between words and music. The intertwining of the act of speaking with that of singing is constantly found in the concerns of the creators in ancient monody, Greek declamation, Gregorian chant, in the polyphonic style, in the opera performance as well as in all the ramifications of the vocal genre.